2018
DOI: 10.1186/s12917-018-1330-6
|View full text |Cite|
|
Sign up to set email alerts
|

Mixed-method tutoring support improves learning outcomes of veterinary students in basic subjects

Abstract: BackgroundTutoring is a useful tool in the university teaching-learning binomial, although its development is impaired in large classes. Recent improvements in information and communication technologies have made tutoring possible via the Internet. The aim of this study was to evaluate the efficacy of mixed-method academic tutoring in two basic subjects in Veterinary Science studies at the University of León (Spain) to optimize the usefulness of tutoring support in the college environment. This quasi-experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…The integration of communication and coping skills and leadership, within education in the curricula of veterinary schools may improve the present situation [45,46]. On-line learning resources [47] together with online tutoring support [48] can incorporate student-centered learning in basic subjects which can help students to overcome stress. Communication skills can also be effectively taught in experimental learning, discussions, and feedback through role-play in small groups of students using simulated clients and trained facilitators [49].…”
Section: Plos Onementioning
confidence: 99%
“…The integration of communication and coping skills and leadership, within education in the curricula of veterinary schools may improve the present situation [45,46]. On-line learning resources [47] together with online tutoring support [48] can incorporate student-centered learning in basic subjects which can help students to overcome stress. Communication skills can also be effectively taught in experimental learning, discussions, and feedback through role-play in small groups of students using simulated clients and trained facilitators [49].…”
Section: Plos Onementioning
confidence: 99%
“…A study investigating student perceptions of online lectures reported that the more satisfied the students are with online classes, the more the positive learning experience, 31 and a positive relation has also been found between the student satisfaction with e-learning, particularly the flipped learning format, and examination scores and performance. [32][33][34] Globally, the present study investigated e-learning acceptance among participants in introductory and advanced training courses in LAS, using a cross-sectional approach focusing on students after introducing the blended learning model. For this purpose, a questionnaire was developed on basis of existing instruments for e-learning evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Various settings are available for teaching EbM skills: classic frontal teaching [6,13], PBL-setting (ProblemBased-Learning) [14], e-learning with tutorial support [5,[15][16][17][18] or Blended Learning [19]. According to the current study situation, an e-learning-setting with tutorial support is suitable for teaching EbD and seems not be inferior to a faceto-face teaching format [17,20].…”
Section: Introductionmentioning
confidence: 93%
“…Students wish to engage in interactivity [15], which means to enter into a dialogue with a lecturer or tutor in order to receive individual feedback on their performance and knowledge progress. The advantage of such a tutorial-supported online measure is also shown in a higher increase in knowledge of a group compared to groups with no tutorial guidance [16]. The tutor must fi nd the balance between the targeted provision of information and the promotion of self-study [21].…”
Section: E-learning Tutormentioning
confidence: 99%